Conjunctival ultraviolet autofluorescence as a biomarker of outdoor time in myopic children - de la Puente, Miriam; Bilbao-Malavé, Valentina; González-Zamora, Jorge; Claici, Aura Ortega; Bezunartea, Jaione; Gomez-Arteta, Leire; Alonso, Elena; Hernández, María; Fernández-Robredo, Patricia; de Viteri, Manuel Sáenz; Calvo, Nerea Martín; García-Layana, Alfredo; et al. (Frontiers in Medicine, 2024)
The prevalence of myopia has increased significantly in recent years including an earlier onset of myopia development on the pediatric population. The main objective of the study is to compare CUVAF (Conjunctival Ultraviolet Autofluorescence) in children with and without myopia to validate its usefulness as an outdoor protective biomarker.A case-control observational study was conducted in a child cohort from subjects that attended to the Ophthalmology Department of Clínica Universidad de Navarra for an ophthalmological examination. The general exclusion criteria were (among others): amblyopia, congenital myopia, general ophthalmic disease, and any conjunctival alteration that might difficult the measurement of the CUVAF area. All participants underwent an automatic objective refraction under cycloplegic effect, biometry to measure axial length (AL) and central corneal radius (CCR), and completed a questionnaire about their lifestyle habits. A total of 4 images of the bulbar conjunctiva were taken with blue light in order to quantify the CUVAF area.Results: A total of 263 subjects (6 to 17 years old) were analyzed with no significant differences in demographic data between case group and control group. There were 50 nonmyopic subjects (19%) and 213 myopic subjects (81%). In relation to the outdoor activities (OA), myopic subjects spent significantly fewer hours per week outdoors than the controlgroup (p=0.03). About the CUVAF area, the differences between groups were statistically significant, showing that the myopic group has a significantly smaller CUVAF area than the control-group (0.33±0.72 mm² vs. 0.78±1.22 mm²; p=0.0023), likewise, the frequency of CUVAF area absence between both groups showed an odds ratio (OR) of 2.52 (CI95% 1.33 -4.74). A Pearson correlation test was done, obtaining a strong significant inverse correlation between myopia degree-CUVAF area (r=0.1877;IC95% 0.068-0.302), and also ratio (AL/CCR)-CUVAF area (p=0.002 and p=0.04) respectively).CUVAF is a useful biomarker for OA and it has an inverse relationship with myopia degree also in pediatric age, especially after the age of 12, so it could be useful to differentiate the risk of developing myopia. Having a CUVAF area greater than that corresponding to age, protect to myopia 2.5 times, being almost 5 times the protection in case of high myopia.